The answer is 9 because half of 14 is 7, and 7+2=9
Answer: 27x²yz + 3xz² - 2xy - 2y²z + 2yz²
<u>Step-by-step explanation:</u>
Use the distributive property.
3xz(9xy + z) - 2yz(x + y - z)
= 3xz(9xy) + 3xz(z) -2yz(x) -2yz(y) -2yz(-z)
= 27x²yz + 3xz² -2xy -2y²z +2yz²
Answer:
17.37
Step-by-step explanation:
y varies inversely as the square root of x
Mathematically:
y = k.root x
We first find k here
To find k, we were made to know that y is 21 and x = 361
k = y/root.x
k = 21/root. 361
k = 21/19
now what is y when x = 247
From y = k.root x
y = 21/19 * root 247
y= 21/19 * 15.72
y = 17.37
2:3
lol thanks for the points
The answer would be 49 + 42b if you multiply 7*7 and 7*6b